2021
DOI: 10.1016/j.ajpath.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Blood Vessels in the Neurologic Manifestations of Coronavirus Disease 2019 (COVID-19)

Abstract: SARS-CoV-2 was originally identified as an outbreak in Wuhan, China towards the end of 2019 and quickly became a global pandemic, with a large death toll. Originally identified as a respiratory disease, similar to previously discovered SARS and MERS type viruses, concern has since been raised about the effects of SARS-CoV-2 infection on the vasculature. This viral-vascular involvement is of particular concern with regards to the small vessels present in the brain, with mounting evidence demonstrating that SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 96 publications
(185 reference statements)
0
12
0
1
Order By: Relevance
“…Finally, the contribution of Kim and Whitmore reviews the rapidly evolving field of vascular consequences of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 11 As noted in this article, the next few years will tell us more about intriguing neurovascular effects of SARS-CoV-2 and how they impact cognition.…”
Section: Q8mentioning
confidence: 90%
“…Finally, the contribution of Kim and Whitmore reviews the rapidly evolving field of vascular consequences of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 11 As noted in this article, the next few years will tell us more about intriguing neurovascular effects of SARS-CoV-2 and how they impact cognition.…”
Section: Q8mentioning
confidence: 90%
“…COPD patients who are former smokers tend to exhibit the highest mortality associated with COVID-19 infection [15][16][17]. The pathophysiological mechanisms by which smoking increases the risk of developing complications from COVID-19 include impaired innate and adaptive immune responses and impairment of the lungs' self-cleansing defense mechanisms [25,26] (Table 1). Inhaled steroids in COPD do not increase susceptibility to viral infection and that in any case; the prescribed basal therapy should not be abandoned during a coronavirus pandemic.…”
Section: Copd Exacerbates Severity Of Covid-19mentioning
confidence: 99%
“…It is important to highlight the pathogenic role of endothelitis associated with diffuse infection and inflammation of the endothelium, which can lead to activation of the coagulation system and the complement cascade, resulting in vascular injury and thromboembolism, ischemia, thus increasing further organ damage in patients [22,23]. A recently recognized important feature of COVID-19 is the abnormal activation of the coagulation system, which clinically predisposes to arterial and venous thromboembolism [24][25][26][27][28]. The degree of coagulopathy is proportional to the severity of the disease and thromboinflammatory biomarkers predict worse outcomes [29].…”
Section: Copd Cigarette Smoking and Ace-2 Expressionmentioning
confidence: 99%
“…A recent report from genomic studies suggested that the genetic sources of α- and β-coronaviruses (CoVs) were derived from bats and rodents, and from an avian host in the case of δ- and γ-CoVs [ 11 ]. Moreover, about seven human CoVs have been recognized that potentially cause mild-to-severe diseases (including neurological disease) in various animal species such as cats, camels, and cows (including cattle) [ 12 ]. Alarmingly, recent scientific evidence has shown that these CoVs are accountable for nearly 10% of acute respiratory infections [ 11 , 13 ], and about 15% of individuals infected by members of the genus β-CoVs (i.e., SARS-CoV-2 and Middle East respiratory syndrome coronavirus (MERS-CoVs)) will develop severe disease, among whom 6% become critically ill [ 11 , 14 ].…”
Section: Covid-19 and The Incidence Of Ischemic Strokementioning
confidence: 99%